Teacher Professional Development Management at Vocational High School - Sumilat, Meiny C.; Lengkong, Jeffry SJ; Mongdong, Romi J. (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study aims to describe and analyze: (1) Planning, (2) Organizing, (3) Actuating, (4) Controlling. This type of research is conducted using a qualitative approach with phenomenological theory and data collection techniques used are observation, interviews and documentation. Data analysis uses the Triangulation method. The results of this study explain that: (1) Planning management of teacher professional development planning at State Vocational High School 1 Ratahan can go through several stages, including: preparation of planning designed with reference to the school's education report, preparation of teacher development training programs to participate in training, workshops/seminars, IHT, MGMP, teacher internships, comparative studies in teacher professional development, allocating a special budget for teacher professional development each year, annual work plan preparation techniques to ensure that educational goals can be achieved effectively and efficiently provide quality education and in accordance with expectations; (2) Organizing management of the organization of teacher professional development at State Vocational High School 1 Ratahan by the principal can go through several stages, including: structuring the organizational structure into the school organizational structure, dividing teacher tasks so that they are directed in carrying out tasks, coordinating through teacher council meetings and work teams to support teacher professional development activities; (3) Actuating of teacher professional development at State Vocational High School 1 Ratahan can go through several stages, including: utilization of documents based on regulations of the Ministry of Education and government regulations, implementing training activities, workshops/seminars, IHT, MGMP, teacher internships, comparative studies, implementation of activities carried out in stages and periodically according to the established plan, involvement of supervisors, principals, vice principals, heads of expertise programs, and teacher representatives. utilization of adequate facilities as a means for teachers to seek information in teacher professional development; (4) Controlling supervision of teacher professional development at State Vocational High School 1 Ratahan by the principal can go through several stages, including: monitoring and supervision of development carried out directly and periodically, performance evaluation to assess the abilities and skills and effectiveness of teachers in teacher professional development.